Learning English Vocabulary with Crossword Media for Early Childhood - Widyahening, Christiana Evy Tri; Sufa, Feri Faila (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine whether Crossword media can improve the mastery of early childhood at an early childhood education institution toward English Vocabulary; and to find out the implementation of Crossword as a media in improving mastery of English Vocabulary at an early childhood education institution. This research is a Classroom Action Research which was conducted from March 2023 to April 2023 by using Crossword as the media. Crossword is able to improve the ability of early childhood in mastering English vocabulary optimally. This can be seen from the pre-test result of 85,77, post-test 1 in cycle one result of 83,85, and post-test 2 result in cycle two of 86,15. Therefore, it can be concluded that Crossword is an effective learning media to be used in improving early childhood English vocabulary mastery.